Osseous Variants of the Cervical Spine with Potential Pathological Significance: Possible Evidence of Vertebrobasilar Insufficiency in a Skeletal Sample from the Post-Classical Cemetery of Corfinio (12th–15th Centuries CE, L’Aquila, Italy) - Anabel Amores; Carmen Tanga; Maria Carla Somma; Vasco La Salvia; Sonia Antonelli; Joan Viciano (Heritage)
The vertebral arteries supply blood to the upper spinal cord, brainstem, cerebellum, and posterior part of the brain. These arteries are susceptible to deformation from external factors such as muscular, ligamentous, or bony structures, and any interruption of blood flow may result in vertebrobasilar insufficiency. Among the osseous variants of the cervical spine with potential pathological significance, variations in the number, shape, and size of the foramen transversarium, as well as the presence of bony bridges in the first cervical vertebra, may suggest a predisposition to vertebrobasilar insufficiency. A skeletal sample from the post-Classical cemetery of Corfinio (12th–15th centuries CE; L’Aquila, Italy) was examined. Regarding the morphology of the foramen transversarium, shape variations were identified in 32 of the 108 vertebrae analysed (a prevalence of 29.6%). Particularly noteworthy are three findings in the atlas: (i) a high prevalence of foramen transversarium variants (35.7% for hypoplastic and double foramina), (ii) a coefficient of roundness consistent with a brachymorphic shape, and (iii) a high prevalence of bony bridges —especially ponticulus posticus (52.9%) and retrotransverse foramen (64.7%). All of these findings may indicate a predisposition to vertebrobasilar insufficiency in the individuals studied. It is hypothesised that external mechanical factors, such as carrying heavy loads on the head, neck, and shoulders due to work activities, along with possible genetic influences related to kinship, may have contributed to the high prevalence of these osseous variants.